Evidence of Improved Vascular Function in the Arteries of Trained but Not Untrained Limbs After Isolated Knee-Extension Training - Bisconti, Angela Valentina; Cè, Emiliano; Longo, Stefano; Venturelli, Massimo; Coratella, Giuseppe; Shokohyar, Sheida; Ghahremani, Reza; Rampichini, Susanna; Limonta, Eloisa; Esposito, Fabio (Frontiers in Physiology, 2019)
The endothelial function is a strong marker of cardiovascular health and it refers to the ability of the body to maintain the homeostasis of vascular tone. The endothelial cells react to mechanical and chemical stimuli modulating the smooth muscle cells relaxation. The extent of the induced vasodilation depends on the magnitude of the stimulus. During exercise, the peripheral circulation is mostly controlled by the endothelial cells response that increases the peripheral blood flow in body districts involved but also not involved with exercise. However, whether vascular adaptations occur also in the brachial artery as a result of isolated leg extension muscles (KE) training is still an open question. Repetitive changes in blood flow occurring during exercise may act as vascular training for the vessels supplying the active muscle bed as wells as for the vessels of body districts not directly involved with exercise. This study sought to evaluate whether small muscle mass (KE) training would induce improvements in endothelial function not only in the femoral (the artery of the limb directly involved with training) but also in the brachial artery (not directly involved with training) as an effect of repetitive increments in the peripheral blood flow during training sessions also in the upper limbs. Ten young healthy participants (5 females, and 5 males; age: 23±3 yrs.; stature: 1.70±0.11 m; body mass: 66±11 kg; BMI: 23±1 kgm-2) underwent an 8-week KE training study. Maximum work rate (MWR), vascular function and peripheral blood flow were assessed pre- and post-KE training by KE ergometry, flow mediated dilatation (FMD) in the brachial artery (non-trained limb), and by passive limb movement (PLM) in femoral artery (trained limb), respectively. After 8 weeks of KE training, MWR and PLM increased by 44% (p=0.015) and 153% (p<0.003), respectively. Despite acute increase in brachial artery blood flow during exercise occurred (+25%; p<0.001), endothelial function did not change after training. Eight weeks of KE training improved endothelial cells response only in the femoral artery of the lower limb directly involved with training, without affecting the endothelial response of the brachial artery not involved with training.